SAR Calculation in a Child Seven-Layer Head Model at 2.1 and 2.6 GHz - Ghusoon Abduljaleel Ahmed; Adheed H. Sallomi (Wasit Journal of Computer and Mathematics Science, 2023)
Health and safety concerns have grown in recent years due to the increasing frequency bands and the demand for wireless communication apparatus. Electromagnetic (EM) radiation breakthrough from Radio frequency (RF) into the human head is an issue that needs to be addressed. Radiation from RF sources can cause serious biological hazards inside the human body. This study measures the average Specific Absorption Rate in a 7-year-old child's head tissues using the ANSYS HFSS software and varying the distance from the source to the antenna in order to address these issues. SAR levels of phones sold should be below certain standard limits. We have used an internal antenna of a mobile phone It's a planar inverted F-antenna (PIFA) with a connected feeding structure.